Simulating graphene dynamics in synthetic space with photonic rings - Danying Yu (Nature Portfolio, 2021)
Photonic honeycomb lattices have attracted attention for their interesting optical properties, but are complicated to reconfigure after fabrication. This work proposes to reduce this complexity to a 1D ring-resonator array by using only one real dimension and one synthetic dimension.